Pengembangan Instrumen Penilaian Berbasis Proficiency Test Untuk Pendidikan Kesetaraan Paket C - Komar, Oong; Kustiawati, R. Tati; Mutakim, Jaenal (Jayapangus Press, 2025)
The Community Learning Center (PKBM), through its Paket C program, plays a vital role in providing equality education for individuals unable to access formal schooling. This study aims to develop a proficiency test -based assessment instrument designed to holistically evaluate the competencies of Paket C learners. The instrument assesses mastery of academic material, functional skills, and entrepreneurial abilities, which are distinctive features of the Paket C program. The research adopts a qualitative approach, utilizing observation to create test specifications, blueprints, and items tailored to appropriate difficulty levels, discrimination indices, and distractor functions. The findings indicate that proficiency test s address the limitations of the current assessment system, which primarily focuses on standardized examinations, by offering a more comprehensive, valid, and relevant evaluation aligned with workforce demands. Moreover, the flexible scheduling and needs-based approach of Paket C education provide broader access for working individuals or those who have not completed formal education. Proficiency test s also ensure the fulfillment of Graduate Competency Standards (Standar Kompetensi Lulusan or SKL) through assessments that integrate Competency Credit Unit (SKK)-based curricula and the evaluation of applied skills. The study recommends the adoption of proficiency test s as an integral part of Paket C's educational evaluation system to create a more inclusive, adaptive, and relevant assessment model that aligns with the learners' needs and the challenges of the modern workforce.